(untitled) - Ceynowa, Klaus (Munchen, 2003)
The cost accounting guidelines of this volume were developed through a project sponsored by the university libraries in Munster and Paderborn, Germany. The cost accounting methods were conceived as part of the fiscal framework of the main service institutions at universities. Methods for forecasting
Keywords: Library finance,Academic libraries,Cost accounting,Academic libraries,Tài chính thư viện,Kế toán chi phí,Thư viện trường đại học,Thư viện trường đại học; Accounting,Computer programs,Accounting,Chương trình máy tính,Kế toán,Kế toán; Germany (West),Tây Đức